2015
DOI: 10.3892/ol.2015.3788
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic gastric carcinoma from breast cancer mimicking primary linitis plastica: A case report

Abstract: Metastases to the gastrointestinal tract rarely occur in breast cancer except in invasive lobular carcinoma. The present study reports a rare case of metastatic gastric cancer from invasive ductal carcinoma (IDC) of the breast mimicking primary gastric linitis plastica. A 51-year-old premenopausal female, who had a history of partial mastectomy for right breast cancer at the age of 40, was referred to Toyama City Hospital (Toyoma, Japan) for an endoscopic diagnosis of gastric linitis plastica. Abdominal comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…The most common histological pattern found in gastric metastasis is adenocarcinoma with signet ring cells; this pattern can be confused with primary gastric cancer, as said in the reviews; indeed in three case reports [37][38][39] preoperative findings showed this pattern on gastric biopsies and surgical treatment was performed.…”
Section: Part 3 Comparison Between Reviews and Case Reportsmentioning
confidence: 88%
See 2 more Smart Citations
“…The most common histological pattern found in gastric metastasis is adenocarcinoma with signet ring cells; this pattern can be confused with primary gastric cancer, as said in the reviews; indeed in three case reports [37][38][39] preoperative findings showed this pattern on gastric biopsies and surgical treatment was performed.…”
Section: Part 3 Comparison Between Reviews and Case Reportsmentioning
confidence: 88%
“…Gastric metastases usually occur many years after primary breast cancer, so when the patient presents with these vague symptoms it's difficult to reconduct them to the primary causative disease. In our case reports, nine [23,28,29,35,37,38,39,43,45] of the patients had a wrong initial diagnosis and they were submitted to surgical treatment in the suspect of a primary gastric cancer.…”
Section: Symptomsmentioning
confidence: 91%
See 1 more Smart Citation
“…On 2014, a systematic review on gastric metastases of different origin has been performed, including data of 4 case series and 2 case reports on breast cancer metastases in the stomach, accounting for a total of 95 patients (4). Our literature search found further 13 publications, including 5 case series and 8 case reports, with a total of 63 patients (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Therefore, by adding our case, data of 159 patients with gastric metastasis from breast cancer are available.…”
Section: Literature Reviewmentioning
confidence: 99%
“…
plasm and gastric metastasis from another organ may be difficult [3], and the conjugation of clinical history, endoscopic findings, histology, and immunohistochemistry is crucial [4].Our patient was a 77-year old female with hypertension, dyslipidemia, hypothyroidism, osteopenia, and a history of hysterectomy and bilateral oophorectomy due to uterine fibroids. She had a bilateral lobular breast carcinoma without distant metastasis (M0) in 1993, treated with right quadrantectomy (pT1N0), left radical mastectomy (pT4N1, with lymphatic invasion), bilateral adjuvant radiotherapy, and adjuvant hormonotherapy with tamoxifen during 5 years.
…”
mentioning
confidence: 99%